Population genetic structure of banana corm weevil Cosmopolites sordidus (Germar) in India - Sunil Kumar, L.; Singh, J. (Journal of asia-pacific entomology, 2018)
The population genetic structure of Cosmopolites sordidus (Germar), an economically important pest of bananas, was studied using the sequence data of the internal transcribed rDNA (ITS1+ITS2) and the mitochondrial ‘COI-tRNALeu-COII’ region from seventy nine individuals collected from six sampling locations in India. The ITS data revealed 70% within population variation and non-significant genetic differentiation estimates suggesting lack of phylogeographic sub-structuring. 49% within population variation and highly significant genetic differentiation values were obtained with the mitochondrial data. The Mantel test revealed lack of correlation between genetic and geographic distance with both the markers. Demographic expansion of the populations was confirmed by the star shaped haplotype networks, demographic tests and mismatch distribution curves using both the markers. Molecular diversity indices show a high haplotype diversity (Hd) but low nucleotide diversity (π) suggesting that the populations are closely related. Considering the low self-dispersal ability of the weevils, these results suggest that the range expansion of this banana pest in India has taken place mainly through transport of infested corms and plant material resulting in the weevils forming localised populations which are not genetically distinct from each other. The high gene diversity (Hd) has enabled the weevils to adapt to varying environmental conditions which could explain the range expansion of this pest in India. The observed discrepancy in the genetic differentiation estimates using these two markers can be attributed to the evolutionary dynamics of the nuclear and mitochondrial genomes.